A review of the design and clinical evaluation of the ShefStim array-based functional electrical stimulation system. Issue 11 (November 2016) - Kenney, Laurence P.; Heller, Ben W.; Barker, Anthony T.; Reeves, Mark L.; Healey, Jamie; Good, Timothy R.; Cooper, Glen; Sha, Ning; Prenton, Sarah; Liu, Anmin; Howard, David
Highlights: The development of an array-based stimulator for drop foot correction is reviewed. The full system design and evaluation process is presented. The final design has been shown to be usable by people with drop foot. Abstract: Functional electrical stimulation has been shown to be a safe and effective means of correcting foot drop of central neurological origin. Current surface-based devices typically consist of a single channel stimulator, a sensor for determining gait phase and a cuff, within which is housed the anode and cathode. The cuff-mounted electrode design reduces the likelihood of large errors in electrode placement, but the user is still fully responsible for selecting the correct stimulation level each time the system is donned. Researchers have investigated different approaches to automating aspects of setup and/or use, including recent promising work based on iterative learning techniques. This paper reports on the design and clinical evaluation of an electrode array-based FES system for the correction of drop foot, ShefStim. The paper reviews the design process from proof of concept lab-based study, through modelling of the array geometry and interface layer to array search algorithm development. Finally, the paper summarises two clinical studies involving patients with drop foot. The results suggest that the ShefStim system with automated setup produces results which are comparable with clinician setup of conventional systems. Further, the final study demonstrated that patients can use the system without clinical supervision. When used unsupervised, setup time was 14 min (9 min for automated search plus 5 min for donning the equipment), although this figure could be reduced significantly with relatively minor changes to the design.